Quality Improvement of 20 KV Voltage Profile Of PT. PLN (Persero) Ketapang According to SPLN No.72 Of 1987 - Fitriah Husin; Bonar Sirait (ELKHA : Jurnal Teknik Elektro, 2022)
This study aims to determine the magnitude of the increase in the voltage profile of the 20.kV distribution network system of PT. PLN (Persero) Ketapang with the installation of reactive power injection equipment. The research method used is the Newton Raphson power flow method with MATLAB simulation program. From the results of these calculations, Pawan 2 and Pawan 6 load buses each have a voltage drop above 5%, which is found on 42 buses. To overcome this, reactive power injection (Qc) was carried out: 150 KVAR on bus 26 of Pawan 2, and 900 KVAR on bus 40 and 46, and 600 KVAR on bus 51 of Pawan 6. This leads to the increase in voltage drop percentage on Pawan 2 and Pawan 6, thus, the profile meets SPLN No. 72 of 1987, which is below 5%.